Masculinities in Play
XIX, 291 p. 12 illus., 8 illus. in color.
Keywords: This volume addresses the persistent and frequently toxic associations between masculinity and games. It explores many of the critical issues in contemporary studies of masculinity—including issues of fatherhood, homoeroticism, eSports, fan cultures, and militarism—and their intersections with digital games, the contexts of their play, and the social futures associated with sustained involvement in gaming cultures. Unlike much of the research and public discourse that put the onus of “fixing” games and gaming cultures on those at its margins—women, LGBTQ, and people of color—this volume turns attention to men and masculinities, offering vital and productive avenues for both practical and theoretical intervention.